Optical Activity Measurements by Interferometry-Diffraction Technique: Test with BSO Crystals - Rueda, Jorge Enrique; Pabón, Dudbil Olvasada; Rueda, Pedro Enrique (Photonics Letters of Poland, 2014)
To measure the optical rotation of a material, we propose a technique which we couple Mach-Zehnder interferometer and an optical Fourier processor 2F. The method uses the dependence of the contrast of the interference fringes with the angle between the planes of polarization of the two beams of the interferometer. The technique allows following the dynamic variations of optical activity, directly observing the changes in the intensity of the diffraction orders in the exit plane of the Fourier processor 2F. We present results. Full Text: PDF References L. A. Nafie, Vibrational Optical Activity: Principles and Applications (Noida, John Wiley & Sons Ltd 2011). CrossRef W. Yang, P R. Griffiths, G. J. Kemeny, "Vibrational Circular Dichroism Measurements by Optical Subtraction FT-IR Spectrometry", Applied Spectroscopy 38, 37 (1984). DirectLink L. P. Polavarapu, Vibrational spectra: principles and applications with emphasis on optical activity (Amsterdam, Elsevier 1998). L. Barron, Molecular light scattering and optical activity (New York, Cambridge University Press 2004). D. Tsankov, A. Polyanichko, H. Wieser, 1 Vibrational Circular Dichroism: Ensuring Quality of Pharmaceutical Products. Pharmaceutical Sciences Encyclopedia. 1, (2011). S. Zhang, Z. Tian, Q. Wang, X. Yin, S. Li, "Optimal length of an electro-optical Q-switch with optical activity crystal La3Ga5SiO14", Optics & Laser Technology 39, 507 (2007). CrossRef E. Shamonina V.P. Kamenov, K.H. Ringhofer, G. Cedilnik, A. Kießling, R. Kowarschik, D.J. Webb, "Optical activity in photorefractive Bi12TiO20 ", Optics Communications 146, 62 (1998). CrossRef V. Marinova, "Optical properties of Bi12TiO20 doped with Al, P, Ag, Cu, Co and co-doped with Al+P single crystals", Optical Materials 15, 149 (2000). CrossRef R.M. Ribeiro, A.B.A. Fiasca, P.A.M. dos Santos, M.R.B. Andreeta, A.C. Hernandes, "Optical activity measurements in the photorefractive Bi12TiO20 single crystal fibers", Optical Materials 10, 201 (1998). CrossRef D.G. Papazoglou A.G. Apostolidis, E.D. Vanidhis, "Index of refraction, optical activity and electro-optic coefficient of bismuth titanium oxide (Bi12TiO20)", Applied Physics B 65, 499 (1997). CrossRef X. He, H. Zhou, W. Zhou, Z. Hu, C. Zhang, H. Huo, J. Wang, Y. Zuo, F. Lu, "Solubility and optical activity of Bi12SiO20 crystals", Journal of Crystal Growth 351, 182 (2012). CrossRef V. Tassev G. Diankov, M. Gospodinov, "Optical activity of doped sillenite crystals", Materials Research Bulletin 30, (10), 1263 (1995). CrossRef V. Tassev, M. Gospodinov, M. Veleva, "Optical activity of BSO crystals doped with Cr, Mn and Cu", Optical Materials 13, 249 (1999). CrossRef J. E. Rueda-P, A. L. Becerra, "Characterization of Reflective TN-LCD, Tuned in Phase-Only Modulation and to Six Wavelengths", Photonics Letters of Poland, 2(4), 174 (2010). CrossRef L.A. Guerra, J.E. Rueda, Master's thesis in Physics, Dynamic Holography using photorefractive materials Bi12SiO20 and LiNbO3 (Universidad de Pamplona, Colombia, 2011) E. Hecht, Optics, Chapter 12. Basics of coherence theory (Addison Weley, 2002).